Enhancing the health and wellbeing benefits of biodiversity citizen science - Oh, Rachel R. Y.; Fuller, Richard A.; Peters, Birte; Dean, Angela J.; Pachana, Nancy A.; Callaghan, Corey T.; Sockhill, Nicola J.; Bonn, Aletta; Suarez-Castro, Andres F. (Frontiers in Environmental Science, 2024)
Engagement in biodiversity citizen science initiatives can confer health and wellbeing benefits to individuals and communities. Yet, few biodiversity citizen science initiatives are explicitly planned to optimize health and wellbeing as a potential co-benefit, leading to missed opportunities for biodiversity conservation and human health. In this perspective, we use a dose-response approach to discuss the components that determine how engagement in biodiversity citizen science initiatives map onto opportunities to foster health and wellbeing benefits. We considered aspects related to the duration and frequency of contact with nature, and the intensity of interactions with nature and between individuals to highlight the different health benefits across the variety of citizen science initiatives. To illustrate these aspects, we use a sample of 95 citizen science initiatives from seven English and non-English-speaking countries and show how careful project design can increase the potential to confer health and wellbeing benefits to participants. We conclude with considerations on how to enhance the health and wellbeing benefits from citizen science initiatives, and propose potential research avenues to assess synergies and trade-offs between benefits to biodiversity and human health from these initiatives.